2012
DOI: 10.1007/s10863-012-9474-8
|View full text |Cite
|
Sign up to set email alerts
|

Functional production of the Na+ F1FO ATP synthase from Acetobacterium woodii in Escherichia coli requires the native AtpI

Abstract: The Na(+) F(1)F(O) ATP synthase of the anaerobic, acetogenic bacterium Acetobacterium woodii has a unique F(O)V(O) hybrid rotor that contains nine copies of a F(O)-like c subunit and one copy of a V(O)-like c(1) subunit with one ion binding site in four transmembrane helices whose cellular function is obscure. Since a genetic system to address the role of different c subunits is not available for this bacterium, we aimed at a heterologous expression system. Therefore, we cloned and expressed its Na(+) F(1)F(O)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 38 publications
1
41
0
Order By: Relevance
“…Similar results were observed with the Na ϩ -coupled rotor of Acetobacterium woodii (24). The current observations were closer to those of Matthies et al (15), who reported that the absence of AtpI reduced the yield, but did not preclude formation, of functional ATP synthase obtained from a cell-free expression system using a plasmid with atp genes from Caldalkalibacillus thermarum TA2.A1.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar results were observed with the Na ϩ -coupled rotor of Acetobacterium woodii (24). The current observations were closer to those of Matthies et al (15), who reported that the absence of AtpI reduced the yield, but did not preclude formation, of functional ATP synthase obtained from a cell-free expression system using a plasmid with atp genes from Caldalkalibacillus thermarum TA2.A1.…”
Section: Discussionsupporting
confidence: 92%
“…The single YidC found in E. coli can be depleted but deletion of yidC is lethal (20,21), and Bacillus subtilis, which has two yidC homologues, yqjG and spoIIIJ, can spare one of them but not both without losing viability (22,23). It is possible that AtpI plays a more indispensable role in assembly of Na ϩ -coupled than H ϩ -coupled ATP synthases; a requirement for AtpI similar to that described by the Yoshida group was recently reported for the Na ϩ -coupled ATP synthase of Acetobacterium woodii in a heterologous system (24). Further, a plausible explanation for dispensability of YidC homologues for c-rotor or ATP synthase synthesis in vitro is that the use of a multicopy, inducible plasmid to express atpI and the subunit c-encoding atpE gene or the whole atp operon may artificially bypass the need for additional proteins that play critical roles in vivo (25,26).…”
mentioning
confidence: 62%
“…Thus, the internal Rnf loop accounts for up to 60% of the total amount of ions translocated during this respiration. In sum, 3 mol of Na Considering that the Na ϩ F 1 F 0 -ATP synthase of A. woodii has 10 ion-binding sites (14,16,51), this makes 3.3 ions/ATP, and thus, caffeate respiration yields 0.9 mol of ATP/mol of caffeate. This is in good agreement with the experimental data (21).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a hybrid F 1 F o (F 1 from Bacillus PS3 and F o from P. modestum) expressed in E. coli requires Atp1/ UncI from P. modestum for c-ring formation and coupled ATPase activity (Suzuki et al, 2007). Similarly, functional production of the Na + F 1 F o -ATP synthase from A. woodii in E. coli requires the A. woodii atp1/uncI gene for proper assembly (Brandt et al, 2013). In addition, c-subunit monomers and c-rings copurify together with P. modestum UncI/Atp1 (Suzuki et al, 2007), and oligomerization of P. modestum c-subunits into c 11 -rings is mediated by Atp1/ UncI in vitro (Ozaki et al, 2008).…”
Section: Atcgl160 Is Involved In C-ring Assemblymentioning
confidence: 99%